KOMPARASI KOMPOSTER AEROB DAN ANAEROB SEDERHANA DALAM PENGELOLAAN LIMBAH ORGANIK - Robert Sinaga; Julieta Manurung; Rico Taruna Siregar (JURNAL AGROTEKNOSAINS, 2023)
The next step after designing the composter is to test the performance of the composter. It is very important to observe the composting process find out the optimum type of composter to use both in the rate of composting and the compost produced. The aims of this research was to compare aerobic and anaerobic composters on composting rates and the compost. The method used was quasi-experimental by comparing the performance of the composter both in terms of composting speed, temperature, humidity, degree of acidity, color and smell of the compost. The results showed that anaerobic composting had a better rate (12 days) than the aerobic method (25 days). The composting process using an aerobic composter required a slightly higher temperature (36oC) than an anaerobic composter (32.5oC). The composting process using an aerobic composter has an average humidity value of 60.75 while that of an anaerobic composter is 68.54. Anaerobic composter showed almost the same value as the aerobic method for the degree of acidity. In terms of odor and color measurements, anaerobic composters produced a more pungent odor and a blackish brown color.